PEMETAAN GLOBAL PENELITIAN AKUNTANSI DIGITAL: ANALISIS BIBLIOMETRIK 2000–2025 PADA DATABASE SCOPUS - Judijanto, Loso (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
This study aims to map the global development of the scientific literature in the field of digital accounting using a data-based bibliometric approach from Scopus. With the help of the VOSviewer software, an analysis of keywords, collaboration networks, and thematic trends from relevant publications over the past two decades was conducted. The visualization results show that "digital accounting" is becoming a major center in the research landscape, closely connected to topics such as blockchain, artificial intelligence, digital transformation, and accounting information systems. In addition, there is a shift in focus from initial studies on information technology and digital economy to more cutting-edge disruptive technologies. These findings make an important contribution in understanding the structure of knowledge, the direction of research development, and the potential for collaboration between countries and institutions in the field of digital accounting. The implications include the preparation of future research agendas, strengthening the digital-based accounting education curriculum, and increasing the readiness of practitioners to face digital transformation. Although descriptive, this study serves as a strategic starting point for further exploration in the realm of digital accounting.